Alignment problems of timber production in architecture-engineering-construction projects - Fallahian, Farhad; Rahimian, Farzad Pour; Ibrahim, Rahinah (Universiti Putra Malaysia, 2012)
Due to the negative effects of the carbon-dioxide on the ecosystem, the Architecture-Engineering-Construction industries are looking for the new materials with lower carbon-footprint. One of the best natural materials that can be used in AEC industries is wood and its derivatives. However, due to the physical and chemical properties of timber, the application of it in AEC industries, especially in the process of manufacturing and production, encounter with some difficulties and obstacles; and they are causes of decreasing the speed and increasing the cost of production in AEC industry. The most important problem in the process of off-site manufacturing of the wooden pieces is caused by the differences between dimensions of pieces in drawings with the dimensions of it that need to be set for the workshop machinery. These changes are not only necessary in the process of sawing pieces, but also in the other processes such as assembling and making the details. Therefore, during the process of manufacturing and production of the wooden pieces, there are a lot of changes on the dimensions of a component in the production drawings and they negatively affect the manufacturing process and, hence increasing the cost and delaying in production. The aim of this research was to find and identify the reasons of these changes in order to mitigate the risks. The research adapted a desktop study followed by direct observations in order to identify the major problems and obstacles. The results showed the problems are mostly due to the tacit nature of design knowledge and lack of proper knowledge of the designers about the actual process of timber production. This research is a novice attempt for expediting timber production process in order to leverage sustainable and modern methods of offsite manufacturing oriented construction.